Study on the Error Sources and Uncertainty Analysisof Groundwater Vulnerability Assessment - KONG Mengyuan; ZHONG Huaping; WANG Gaoxu; WU Yongxiang (Renmin Zhujiang)
Through groundwater vulnerability assessment, more efficient and targeted protectivemeasures can be taken into groundwater system, and the limited human resources and funds can beallocated to regions with higher pollution risks to improve the protection efficiency ofgroundwater resources. This paper introduces the concept of groundwater vulnerability, errorsourcesof groundwater vulnerability assessment, significance of assessment uncertainty analysis,application of the first order uncertainty analysis method to groundwater vulnerability assessmentand the difficulties and shortages of the uncertainty analysis, which can provide scientific guideand theoretical support to the study on uncertainty analysis of groundwater vulnerabilityassessment.